Perbedaan pembelajaran e-learning web course berdasarkan hasil belajar matematika di kelas XI - Arigiyati, Tri Astuti; Lilhawa, Rosy Khairunnisa; Taufiq, Irham (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2023)
Media Web Course is the use of the internet for educational purposes, where students and teachers are completely separate and no face-to-face is required. The objectives of this study are: (1) To find out whether there are differences in mathematics learning outcomes based on the e-learning learning method using the web course model (2) To determine whether there are differences in mathematics learning outcomes based on the level of student independence and (3) To determine whether there is an interaction between the e-learning learning method using the web course model and the level of student independence. The method used is an experimental research method. The research design used is a factorial design. The data analysis technique used is two-way analysis of variance. The results of this study are: (1) there is an influence between the use of web-based learning media on student learning outcomes obtained from the analysis of hypothesis testing (2) there is an influence between student learning independence and student learning outcomes (3) there is no interaction between student learning independence and learning outcomes using web media.